Entre ideologias e utopias: visões de mundo dos agricultores agroecológicos do assentamento Celso Furtado em Quedas do Iguaçu-PR - Silva, Emerson Ferreira da (2018)
The MST has agroecology as one of its main flags, along with agrarian reform, and acts for this productive paradigm to be adopted in the settlements in which the Movement has influence. Even so, conventional agriculture still prevails in most settlements. In this work, we analyze the ideological aspects of the subjects practicing or practicing agroecology in order to identify among the elements that make up the social world view of the settlers, those who motivate them or not to practice agroecology. Having as theoretical support the concept of ideology as a social vision of the world, that as a set of thoughts and values that, socially constructed, act to guide the actions of individuals, we choose three world views that act in a significant way on the settlers. These are traditional agriculture, conventional agriculture and the agroecological vision. In order to understand how these worldviews work in the practice of settled peasants, a group of farmers from the Celso Furtado settlement in Quedas do Iguaçu, Paraná, were studied. Among the interviews, we chose eights to be analyzed, four of which were agroecological farmers, two that stopped producing in an agroecological way and two in transition to agroecology. In view of the insufficiency of public policies to promote agroecology, farmers end up being the main responsible for the viability of agroecological projects, but these projects are only continued when the agroecological world view consolidates to the detriment of others, such as conventional or traditional agriculture.